Long-Term Measurements in the Neutral Temperature Identification Problems in Continuous Welded Rail - Vnenk, Petr; Culek, Bohumil (Budapest University of Technology and Economics, 2017)
This paper deals with the problem of determination of neutral temperature in continuous welded rails. It specifies the origin of the problem in the introductory chapter, where historical development of rail-wheel interaction is briefly presented. Later, the paper discusses the issue of stress in continuous welded rail as the major factor by maintaining safety operation of such railway tracks. The stress problems in continuous welded rail are tightly connected to the problem of neutral temperature. The term “neutral temperature” is defined and its attributes presented. The major focus in this part of the article is given to a thorough explanation of the effect of neutral temperature shift, its causes and its detection. In the last chapters, ongoing long-term measurements which are aimed to get important data for further research in the area are described and commented. Potential further challenges are included in the brief conclusion.
Dlouhodobá měření v problémech identifikace neutrální teploty v kolejnici bezstykových kolejí
Keywords: Rail; Temperature; Stress; Climate; Strain Gauge; Kolejnice; teplota; napětí; klima; tensometr